Fear-Avoidance Beliefs and Parental Responses to Pain in Adolescents with Chronic Pain - Anna C Wilson; Amy S Lewandowski; Tonya M Palermo (Pain Research and Management)
BACKGROUND: The fear-avoidance model of chronic pain posits that fear of pain is associated with fear and avoidance of activity, which can lead to deconditioning and persistence of pain and disability. Despite being well supported in adults, little is known about the role of fear-avoidance beliefs regarding physical activity in children. Research has shown that parental protectiveness contributes to activity limitations in children; however, no studies have examined relationships between protectiveness, and fear and avoidance.